1988
DOI: 10.1111/j.1471-0528.1988.tb06867.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fructosamine in non‐diabetic pregnancy

Abstract: Plasma fructosamine and its relation to plasma total protein and albumin was examined in 40 non-diabetic pregnant women. Plasma fructosamine did not correlate with haemoglobin A, or plasma albumin. The mean intra-individual ranges were plasma fructosamine 0.53 mmol/l (SD 0.17); haemoglobin A, 1.42% (SD 0.42); plasma fructosamine/g albumin 0.024 mmol (SD 0.005) and plasma fructosamine/g total protein 0-008 mmol (SD 0-003). A high degree of individuality for these variables was also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…As reported by many others, fructosamine decreases with decrease of serum albumin concentration in advanced pregnancy. 3 Our results showed that total protein was decreased slightly, but significantly, in middle and late pregnancy, suggesting an apparent decrease in the fructosamine level. The fasting plasma glucose and glycated albumin values in the glycosuria group were slightly, but not significantly, higher than those in the normal group.…”
Section: Discussionmentioning
confidence: 60%
“…As reported by many others, fructosamine decreases with decrease of serum albumin concentration in advanced pregnancy. 3 Our results showed that total protein was decreased slightly, but significantly, in middle and late pregnancy, suggesting an apparent decrease in the fructosamine level. The fasting plasma glucose and glycated albumin values in the glycosuria group were slightly, but not significantly, higher than those in the normal group.…”
Section: Discussionmentioning
confidence: 60%